2013
DOI: 10.3174/ajnr.a3627
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Microemboli and Correlation with Platelet Inhibition in Aneurysmal Flow Diversion

Abstract: SUMMARY: Flow-diverting stents have been associated with embolic and hemorrhagic complications, but the rate of procedure-related microemboli is unknown. Using transcranial Doppler sonography, we measured the rate of microemboli in 23 patients treated with flow-diverting stents. Patients received preprocedural dual antiplatelet medications and intraprocedural heparinization. Point-of-care platelet reactivity testing was performed before the procedure, and nonresponders (Ͼ213 P2Y12/ADP receptor reactivity units… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…One study found that all patients were among the expected antiplatelet inhibition rate 33. The remaining studies did not report complications based on antiplatelet testing results, but 20 studies reported the action taken after abnormal results: two studies reported postponing procedures,34 35 three reported modification of the loading dose,36–38 eight reported switching to prasugrel/ticagrelor regimens,14 39–45 and seven studies reported switching to an alternative regimen 46–52. Another eight studies (335 patients) did not conduct antiplatelet testing at all and nine studies with 406 patients did not report the data on its usage (table 2).…”
Section: Resultsmentioning
confidence: 99%
“…One study found that all patients were among the expected antiplatelet inhibition rate 33. The remaining studies did not report complications based on antiplatelet testing results, but 20 studies reported the action taken after abnormal results: two studies reported postponing procedures,34 35 three reported modification of the loading dose,36–38 eight reported switching to prasugrel/ticagrelor regimens,14 39–45 and seven studies reported switching to an alternative regimen 46–52. Another eight studies (335 patients) did not conduct antiplatelet testing at all and nine studies with 406 patients did not report the data on its usage (table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Stent-view CT was used to confirm stent placement and assess for endoleak, which was treated in two cases with balloon angioplasty 24. Transcranial Doppler examinations with emboli monitoring were used to follow patients postoperatively to monitor for potential embolic complications and assess the effectiveness of antiplatelet medications23; no such events were detected.…”
Section: Discussionmentioning
confidence: 99%
“…Relative contraindications to endovascular treatment include antiplatelet medication resistance as indicated by aspirin and clopidogrel assays, size ,10 mm (offlabel use for PED), unreliable or noncompliant patients (for follow-up angiography and medication compliance), extremely tortuous cervical and/or intracranial ICA anatomy, severe stenosis of the intracranial ICA, and patient desire for immediate aneurysm occlusion. 48 In addition, in younger patients (,40 years of age) with surgically accessible and clippable aneurysms, microsurgery is strongly considered, but both endovascular treatment and microsurgical treatment are presented as reasonable options. Certain patients have a strong desire or need (eg, sentinel headaches) for immediate aneurysm obliteration or are reluctant to perform close angiographic follow-up at 6 and 12 months after treatment.…”
Section: Discussionmentioning
confidence: 99%